Gender differences in pre-surgical hip arthroplasty patients - Ripoll-Romero, Elisabet; Agüera, Zaida; Puig-Llobet, Montserrat; Bassas, Marta; Manzanares-Céspedes, Maria Cristina; Galimany-Masclans, Jordi (Frontiers in Global Women's Health, 2025)
IntroductionThere is growing evidence that gender may influence surgical outcomes, rehabilitation, and overall patient experience in various orthopedic procedures. The main objective of the present study was to explore gender-based differences in patients undergoing hip arthroplasty surgery to understand better how they might impact the preoperative experience and contribute to personalized patient care.MethodsA cross-sectional study was conducted with n = 180 pre-surgical participants (n = 84 females, n = 96 males). All patients were consecutively admitted for primary hip arthroplasty surgery at the orthopedics surgery and traumatology unit of the Hospital Clínic of Barcelona (Spain), between October 1, 2023 and July 31, 2024. The assessment consisted of a socio-demographic form and two questionnaires: the Hospital Anxiety and Depression Scale (HADS) and the 5-level EQ-5D version (EQ-5D-5l).ResultsBoth groups consisted of a similar percentage of males and females. Females presented statistically significantly higher levels of preoperative anxiety than males (p = .050), but no significant differences appeared in the depression subscale (p = .382). Regarding quality of life, females reported significantly higher scores on difficulties in mobility (p = .037), usual activities (p = .027), and perceived pain (p = .004) compared to males. Finally, greater anxiety and depression scores were associated with poor self-perceived health in males but not in females.ConclusionsThis study is essential to bridge gaps in knowledge regarding gender differences in patients undergoing hip arthroplasty. Clinically, these results underline the importance of considering gender-specific factors when planning interventions and support for hip arthroplasty patients to improve outcomes and overall well-being.